Effect of Planting Dates on the Yield of Mustard Seed - Alam, M.J.; Ahmed, K.S.; Mollah, M.R.A.; Tareq, M.Z.; Alam, J. (International Journal of Applied Sciences and Biotechnology, 2015)
The experiment was conducted at Shibganj upazila under Bogra district during October, 2014 to January, 2015 to observe the effect of planting dates on the yield of mustard seed. There were five planting dates viz. 25 October, 30 October, 05 November, 10 November and 15 November. Significant variations due to different planting dates were observed in plant height, number of leaves plant-1, number of siliqua plant-1, number of seed siliqua-1, 1000 weight plot-1, yield plot-1and yield ha-1of mustard. Results showed that the highest seed yield was1.50 t ha-1 obtained from 30 October. The lowest seed yield was 1.0 t ha-1 from 15 November. From the results, the best planting date of mustard is on 30 October in the northern parts of Bangladesh. Int J Appl Sci Biotechnol, Vol 3(4): 651-654